Geochemical Characteristics of Hydrocarbons in Core Sediments From the Southwest Sub-Basin of the South China Sea and Its Implications for the Sedimentary Environment - Wang, Xianqing; Wan, Zhifeng; Chen, Chongmin; Chen, Sheng (Frontiers in Earth Science, 2021)
Marine sediments are found to record various information for example the evolution of ocean and the exchange of matter and energy between the surrounding continents and oceans. The Southwest Sub-basin is one of the most important tectonic unit in the South China Sea Basin. The geochemical information of the sediments provides potential to understand the sedimentary history of the Southwest Sub-basin of South China Sea. In this paper, the aliphatic hydrocarbon compounds in two core sediments from the Southwest sub-basin were analyzed using lipid biomarker analysis. The average concentration of the total organic carbon (TOC) and the total nitrogen (TN) for both core sediment A and sediment B are similar, falling in the range of 0.64% ± 0.18 and 0.10% ± 0.02%, respectively. The C/N ratios vary from 3.2 to 11.1, reflecting that the organic carbon was a mixture of terrestrial and marine sources with more contributions from marine sources in core sediment B than sediment A. The long-chain n-alkanes of both core sediments show an even-odd predominance, reflecting the contributions of terrestrial higher plants and short-chain n-alkanes from marine plankton or bacteria. The Pr/Ph of core sediments A and B are 0.3–0.5 and 0.2–0.4, respectively, both of which are far less than 1, indicating that the sedimentary environment was dominated by strong reduction and long-term stability. The odd-even distribution of medium-chain n-alkanes (n-C14–20) in the core sediments A and B is due to the reduction of n-fatty acids with an odd carbon dominance in a strongly reductive depositional environment.